2021
DOI: 10.1016/j.sleep.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The immediate impact of the 2019 novel coronavirus (COVID-19) outbreak on subjective sleep status

Abstract: Background An outbreak of the 2019 novel coronavirus (COVID-19) has been ongoing in China since January 2020. The threat of infection affects the work and life of most of the population and may also damage sleep. This study aims to examine the subjective sleep status and mental health of the population during the peak of the COVID-19 epidemic. Method The data were collected through an online questionnaire with a sample of 5461 individuals in China from February 5, 2020,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
213
6
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(274 citation statements)
references
References 52 publications
(33 reference statements)
26
213
6
15
Order By: Relevance
“…The findings of Lin et al's [3] study have important clinical and public health implications. The immediate psychological impact of the pandemic suggests the need for rapid and concerted interventions to help people in distress cope with the aftermath of this unprecedented crisis.…”
Section: Editorialmentioning
confidence: 95%
See 2 more Smart Citations
“…The findings of Lin et al's [3] study have important clinical and public health implications. The immediate psychological impact of the pandemic suggests the need for rapid and concerted interventions to help people in distress cope with the aftermath of this unprecedented crisis.…”
Section: Editorialmentioning
confidence: 95%
“…The few published studies on this topic focused primarily on healthcare workers and their findings indicated even higher rates of insomnia (34%e36%), anxiety (45%) and depressive symptoms (50%) among those individuals relative to the general population, with the symptoms being more severe among front line workers directly involved with patients diagnosed or at risks for COVID-19 [4,5]. One weakness of the Lin et al's study is that older adults, clearly those most severely affected by this pandemic, represented only 2% of the sample [3]. One might expect significantly higher rates of insomnia and psychological symptoms among this segment of the population.…”
Section: Editorialmentioning
confidence: 95%
See 1 more Smart Citation
“…This is the most widely used tool in community surveys for physical and mental health evaluation (43)(44)(45). Features that might be related to sleep quality evaluated by previous studies were included in the questionnaire (46)(47)(48). Moreover, some hypothesized risk factors of sleep disturbance in the context of COVID-19 and new normal life during the lockdown were also included in the questionnaire.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Unadjusted and adjusted models examining the association between movement behaviors and mental health outcomes for CPAS parents during the pandemic are summarized in Table 5. In adjusted models, lower levels of physical activity and poorer sleep A growing body of research has demonstrated an increase in sleep problems in the general population as a result of the COVID pandemic, [34][35][36][37] however, these studies have not systematically compared rates of sleep problems to pre-pandemic levels and/or have not focused on parents and children specifically. The higher levels of child sleep problems and irregular bedtime reported by parents in the CPAS cohort, and the connection between child sleep problems and indicators of poorer mental health, suggest that sleep may be an important modifiable factor to improve children's functioning during the COVID-19 pandemic.…”
Section: Parentmentioning
confidence: 99%